'BLAST First (from politeness) ENGLAND': The Manifesto in Britain and Ireland. Issue 2 (July 2017) - Hanna, Julian
Abstract : Aside from the familiar story of Vorticists and Imagists before the war, no detailed analysis of manifestos in Britain (or Ireland) exists. It is true that, by 1914, there had been such an upsurge in manifesto writing that a review of BLAST in The Times (1 July 1914) began: 'The art of the present day seems to be exhausting its energies in "manifestoes."' But after the brief fire ignited by the arrival of Italian Futurism died out, Britain again became a manifesto-free zone. Or did it? While a mania for the militant genre did not take hold in Britain and Ireland the same way it did in France, Italy, Germany, or Russia, the manifesto did enjoy a small but dedicated following that included Whistler, Wilde, and Yeats; Patrick Geddes and Hugh MacDiarmid; Wyndham Lewis and Ezra Pound; Dora Marsden and Virginia Woolf; and Auden, MacNeice, and Spender. Through these and other figures it is possible to trace the development of a manifesto tradition specific to Britain and Ireland.